Analysis The Effect Of Service Quality Dimensions On Customer Satisfaction Of Transjakarta Public Transportation - Indra, Farhan Faturrachman; Suyanto, AMA (UNIVERSITAS PAKUAN, 2023)
The issue of traffic congestion in DKI Jakarta remains unsolved by the local government. Data from the Indonesian National Police reveals a continuous rise in motorized vehicles, particularly motorcycles and cars, from 2020 to 2022. This is corroborated by the 2023 rankings from TomTom, which position Jakarta as the 29th most congested city worldwide in terms of traffic. The DKI Jakarta Provincial Government has introduced public transportation options, including the Jakarta MRT, Jakarta LRT, Mikrotrans, and Transjakarta, to address traffic congestion. Transjakarta has gained popularity, carrying over a million passengers daily in August 2022, indicating a growing acceptance of government-owned public transit services. This study aims to assess how various aspects of service quality impact customer satisfaction within the context of Transjakarta public transportation. A sample of 391 respondents was analyzed using multiple linear regression through IBM SPSS 25 software. Data was collected via Google Forms. Findings reveal that several dimensions, including Tangibility, Responsiveness, Assurance, and Empathy, positively influence Customer Satisfaction. However, the Reliability dimension has no significant impact on Customer Satisfaction. Importantly, collectively, the SERVQUAL dimensions (Tangibility, Responsiveness, Reliability, Assurance, Empathy) demonstrably affect Customer Satisfaction with Transjakarta Public Transportation.